Sodium and potassium content of meals served in university canteens - Barbosa, Maria Inês (2021)
ABSTRACT - A high sodium intake is associated with high blood pressure, an important risk factor for noncommunicable diseases (NCDs). In contrast, the ingestion of high levels of potassium counteracts this negative effect of high sodium intake on blood pressure, thus reducing the sodium-to-potassium ratio. The aim of this work was to determine the sodium and potassium content of meals served in university canteens in Portugal. The analysis included 35 samples of soup and 35 samples of main dish collected at 5 random days from a total of 7 university canteens. The samples were analyzed for sodium and potassium by atomic emission spectrometry technique. On average, a meal (soup and main dish) had a sodium content of 1,069.4 mg (mean sodium content was 671.4 ± 374.5 mg/portion in the main dish and 398.0 ± 153.0 mg/ portion in the soup) and a potassium content of 1,004 mg (mean potassium content was 731.4 ± 385.9 mg/serving in the main dish and 272.6 ± 272.6 mg/serving in the soup). Our results revealed that with a single university meal, students can reach 53% of the maximum daily value recommended for sodium and 27% of the minimum daily value recommended for potassium. An investment to decrease sodium and increase potassium in meals served is imperative in order to prevent NCDs.